Respiratory Syncytial Virus Hospitalizations among U.S. Preterm Infants Compared with Term Infants Before and After the 2014 American Academy of Pediatrics Guidance on Immunoprophylaxis: 2012–2016 - Goldstein, Mitchell; Krilov, Leonard R.; Fergie, Jaime; McLaurin, Kimmie K.; Wade, Sally W.; Diakun, David; Lenhart, Gregory M.; Bloomfield, Adam; Kong, Amanda M. (American Journal of Perinatology, 2018)
Objective The objective of this study was to compare risk for respiratory syncytial virus (RSV) hospitalizations (RSVH) for preterm infants 29 to 34 weeks gestational age (wGA) versus term infants before and after 2014 guidance changes for immunoprophylaxis (IP), using data from the 2012 to 2016 RSV seasons.Study Design Using commercial and Medicaid claims databases, infants born between July 1, 2011 and June 30, 2016 were categorized as preterm or term. RSVH during the RSV season (November–March) were identified for infants aged <6 months and rate ratios (RRs) for hospitalization comparing preterm and term infants were calculated. Difference-in-difference models were fit to evaluate the changes in hospitalization risks in preterm versus term infants from 2012 to 2014 seasons to 2014 to 2016 seasons.Results In all seasons, preterm infants had higher RSVH rates than term infants. Seasonal RRs prior to the guidance change for preterm wGA categories versus term infants ranged from 1.6 to 3.4. After the guidance change, the seasonal RRs ranged from 2.6 to 5.6. In 2014 to 2016, the risk associated with prematurity of 29 to 34 wGA versus term was significantly higher than in 2012 to 2014 (P<0.0001 for commercial and Medicaid samples).Conclusion In infants aged <6 months, the risk for RSVH for infants 29 to 34 wGA compared with term infants increased significantly after the RSV IP recommendations became more restrictive.
Keywords: respiratory syncytial virus; immunoprophylaxis; hospitalization rates; palivizumab